Peran Mediator Kepuasan Kerja Pada Faktor-Faktor Yang Mempengaruhi Kinerja Karyawan: Pendekatan Empiris Menggunakan Model SEM-AMOS - Ardian Nur Romadhan; Rina Eka Widjayanti (AKSIOMA : Jurnal Manajemen, 2025)
The purpose of this study was to identify attribute predictors that affect employee performance with job satisfaction as a mediator. This type of quantitative research uses survey data as its source. The number of data samples is 228 harvest workers of Oil Palm Plantations. Data analysis was carried out using SEM-AMOS. The results of the study showed that employee performance was positively influenced by work discipline, compensation, organizational commitment, and job satisfaction. In addition, job satisfaction as a mediator variable as a whole has been proven to be able to see indirect effects on exogenous variables in this study. Research facts prove that job satisfaction is important as a mediator that influences stimuli in the form of predictors of work discipline, compensation, and organizational commitment to the formation of responses in the form of employee performance.